Modifications on the "Soil Conservation Service Method" for the estimation of design floods on very small catchments in the arid western part of the United States of America - Hiemstra, Lourens Abram Viljoen, author; Colorado State University, publisher (Colorado State University. Libraries, 1968)
Modifications are necessary on the so-called "Soil Conservation Method" for the estimation of runoff rates on ungaged catchments to make United States of America. First, a modification was made in the equation for peak rates of runoff to bring the equation in line with sound theoretical analysis. Second, it was shown that the rainfall occurring in a storm with 3D-minute duration is more applicable to the region under consideration than the 6-hour storms used in the unmodified Soil Conservation Method. Third, an expression was found for the optimum storm duration suitable to calculations of peak rates of runoff on any small catchment.
March 1968.
CER68-69LAVH19.
Keywords: Soil conservation -- West (U.S.) -- Mathematical models; Watersheds -- West (U.S.); Floods -- West (U.S.)